2010
DOI: 10.1080/1573062x.2010.484502
|View full text |Cite
|
Sign up to set email alerts
|

Impact of concrete and PVC pipes on urban water chemistry

Abstract: Waterways contain a chemical signature of catchment land use, climate and geology. This is increasingly being influenced by the urban landscape and particularly the composition of materials and activities that occur on impervious surfaces. This paper examines the degree and extent of two types of drainage materials, concrete and PVC, on urban water chemistry. This study found that water collected from a zinc and slate/tile roof and stored in a plastic rain tank (roof water) was acidic (pH 4.79) and had low bic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
50
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(62 citation statements)
references
References 22 publications
4
50
1
Order By: Relevance
“…Urbanisation has been associated with increased alkalinity of riparian soils (Moffatt et al, 2004), thus soil pH may be a proxy for urban development intensity. One potential reason for this is the dissolution of cement products into stormwater conveyed by concrete gutters and pipes (Davies, Wright, Jonasson, & Findlay, 2010). In addition, soil pH is associated intrinsically with the underlying geology.…”
Section: Plantsmentioning
confidence: 99%
“…Urbanisation has been associated with increased alkalinity of riparian soils (Moffatt et al, 2004), thus soil pH may be a proxy for urban development intensity. One potential reason for this is the dissolution of cement products into stormwater conveyed by concrete gutters and pipes (Davies, Wright, Jonasson, & Findlay, 2010). In addition, soil pH is associated intrinsically with the underlying geology.…”
Section: Plantsmentioning
confidence: 99%
“…Dissolution and degradation of concrete also increases when it is subjected to frequent exposure to road salt [122]. As urban karst weathers and dissolves [10,43], calcium and carbonate are released into urban waters influencing alkalinity, water hardness, and pH [118][119][120]123] (Figure 3). Additionally, decomposition of labile organic matter (e.g., sewage) in urban watersheds can also increase inorganic carbon concentrations and bicarbonate alkalinity in urban watersheds [124].…”
Section: Evolving Alkalinization Of Water: Watershed Antacids and Calmentioning
confidence: 99%
“…The chemistry of streams and rivers draining urban areas can be influenced by the dissolution of concrete and other building materials [116,118,119] (Figure 3). For example, cement can contain limestone, gypsum, and other constituents that weather quickly when exposed to acidic water [120]. Rain water is naturally slightly acidic due to the formation of carbonic acid from atmospheric CO2.…”
Section: Evolving Alkalinization Of Water: Watershed Antacids and Calmentioning
confidence: 99%
“…Although there are several possible sources of calcium in the watershed, it is possible that our elevated calcium values are due to the dissolution or chemical weathering of concrete found in the watershed, e.g., structures, other impervious surfaces, and channelized reaches. Several studies have documented the effects of concrete on stream water Table 1. chemistry and its increase in calcium concentrations (Leung and Jiao 2006, Davies et al 2010, Wright et al 2011, Tippler et al 2012. For example, Tippler et al (2012) found that in streams with high imperviousness, calcium concentrations were more than nine times that of less impervious streams (20 mg/L vs. 2.2 mg/ L).…”
Section: Discussionmentioning
confidence: 99%